The Role of Advanced Imaging in Gout Management - Li, Shuangshuang; Xu, Guanhua; Liang, Junyu; Wan, Liyan; Cao, Heng; Lin, Jin (Frontiers in Immunology, 2022)
Gout is a common inflammatory arthritis where urate crystals deposit in joints and surrounding tissues. With the high prevalence of gout, the standardized and effective treatment of gout is very important, but the long-term treatment effect of gout is not satisfied because of the poor adherence in patients to the medicines. Recently, advanced imaging modalities, including ultrasonography (US), dual-energy computed tomography (DECT) and magnetic resonance imaging (MRI) attracted more and more attention for their role on gout as intuitive and non-invasive tools for early gout diagnosis and important monitoring in gout treatment. This review from the hyperuricemia, gout attacks, chronic gout and gout complications, summarized the US, DECT and MRI role on the management of gout, descripted the current scoring systems for quantifying the severity of disease, and discussed about the challenges and limitations of using these imaging tools on assessing the gout treatment response.